DEFERRED REVENUE ACCOUNTING - Valentin Gabriel CRISTEA (Challenges of the Knowledge Society, 2022)
Torosyan and Razani1 said that the Tax Cuts and Jobs Act amended Sec. 451 to allow accrual-basis taxpayers to defer recognizing income until it is considered in their applicable financial statements. This rule eliminates some book-tax timing differences regarding unearned revenue, also known as deferred revenue. Payment made to a buyer for an unearned income account is gross income for the buyer for tax purposes, which is eligible for deferral. The buyer is also required to capitalize the costs of servicing the contracts corresponding to the uncollected revenue, as these are paid as debts incurred in the transaction. A risk problem with deferred revenue in purchase accounting is the tendency for it to vanish during mergers or acquisitions. During the deal, deferred revenue must be recorded at fair value according to GAAP. This is based on what it will cost to deliver the service or goods. The cost is less than the amount that was received for it. When the deferred revenue is adjusted down in purchase accounting, there is a sum that never gets recorded as revenue in the future. We notice, for a supplementary consideration, when there are advance billing customers close to an acquisition this situation has an impact on future revenue recognition.